Implementing constructive alignment in higher education–cross-institutional perspectives from Australia - Ruge, Gesa; Tokede, O.; Tivendale, L. (2019)
Constructive alignment (CA) has become internationally established as an educational approach linking strategic planning and corporate policy to discipline and course teaching and learning practice. The literature to date has focused predominantly on either single institutional or specific discipline settings and curriculum level initiatives. This research study seeks to broaden the conceptual and methodological perspective on constructive alignment with a cross-institutional study from two Australian universities. The case study learnings from a top-down institutional implementation of CA at one university and the bottom-up teaching and learning approach within the other have been jointly investigated. By mapping the implementation process of constructive alignment, the key strengths and constraints for both approaches have been identified. These findings offer new insights for institutional managers as well as academics and teaching and learning professionals. In addition, a potential ‘gap in the middle’ at faculty level is highlighted. It is within this nexus that the transitions from institutional policy and targets to successful discipline-specific teaching and learning practices and outcomes are shaped. This research seeks to raise the awareness that CA design, planning and implementation should be conceptualised from the outset as a dynamic, multi-directional and iterative process, irrespective of whether a predominantly top-down or bottom-up approach for implementation is chosen.